Ukrainian Identity of Lemkos by the Example of Activity of the Defense Organization of Lemko Western Ukraine in America = Ukraińska tożsamość Łemków na przykładzie działalności Organizacji Obrony Łemkowszczyzny w Ameryce - Tyda, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Thee Organization for Defense of Lemko Western Ukraine in America, Inc. (OOL) is one of the oldest and most influential Lemkos organizations in the United States. It was necessary for them to help families in the homeland. Material assistance was donated in large part to Ukrainian schools, churches, artistic ensembles, and Ukrainian educational institutions. OOL was formed in 1936 in Philadelphia and began to publish the monthly "Lemkivskiy Dzvin".
Keywords: Lemko; Lemkivshchyna; Ukraine; identity; organization; Łemkowie; Łemkowszczyzna; Ukraina; tożsamość; organizacja